Multicultural CSR Communication for Achieving a Sustainable Environment - Apriliani, Riski; Cassana, Rona Rizkhy Bunga; Ummah, Khanun Roisatul; Ramadhani, Dinda Safitri; Alhasanain, Nando (Nyimak: Journal of Communication, 2024)
Corporate Social Responsibility (CSR) plays a vital role in fostering an empowered and sustainable society, particularly concerning environmental conservation efforts. This study explores the implementation of CSR communication through a multicultural lens by PT Kilang Pertamina Internasional Refinery Unit II Sungai Pakning, focusing on its "Permata Hijau Pesisir Gambut" program aimed at preserving the environment and protecting coastal areas. Employing a qualitative descriptive method, data were gathered through in-depth interviews, literature reviews, and document analysis. The Miles and Huberman data analysis model was utilized, which encompasses data collection, presentation, and simultaneous conclusion drawing, supported by source triangulation to ensure data validity. The findings indicate that PT Kilang Pertamina Internasional Refinery Unit II effectively adopts the triple bottom line approach of "planet, people, and profit" to attain sustainable development. By integrating multicultural principles, the CSR program aligns with community needs and cultural contexts along the peatland coast. A symmetrical CSR communication model was implemented, incorporating socialization, training, and direct assistance in collaboration with local groups, such as the Harapan Bersama Group, to establish the Mangrove Education Center Ecotourism. This approach exemplifies the effectiveness of culturally adaptive CSR strategies in promoting environmental sustainability.Keywords: CSR Communication, Multicultural, Sustainable Environment, Pertamina AbstrakTanggung jawab sosial perusahaan (CSR) memainkan peran penting dalam membangun masyarakat yang berdaya dan berkelanjutan, terutama dalam upaya konservasi lingkungan. Penelitian ini mengeksplorasi pelaksanaan komunikasi CSR melalui pendekatan multikultural oleh PT Kilang Pertamina Internasional Refinery Unit II Sungai Pakning, dengan fokus pada program "Permata Hijau Pesisir Gambut" yang bertujuan untuk melestarikan lingkungan dan melindungi daerah pesisir. Menggunakan metode deskriptif kualitatif, data dikumpulkan melalui wawancara mendalam, tinjauan pustaka, dan analisis dokumen. Model analisis data Miles dan Huberman digunakan, yang mencakup pengumpulan data, presentasi, dan penarikan kesimpulan secara bersamaan, didukung oleh triangulasi sumber untuk memastikan validitas data. Temuan menunjukkan bahwa PT Kilang Pertamina Internasional Refinery Unit II berhasil mengadopsi pendekatan triple bottom line "planet, people, dan profit" untuk mencapai pembangunan berkelanjutan. Dengan mengintegrasikan prinsip-prinsip multikultural, program CSR ini selaras dengan kebutuhan komunitas dan konteks budaya di sepanjang pesisir lahan gambut. Model komunikasi CSR yang simetris diterapkan, mencakup sosialisasi, pelatihan, dan bantuan langsung bekerja sama dengan kelompok lokal, seperti Harapan Bersama Group, untuk mendirikan Ecotourism Pusat Pendidikan Mangrove. Pendekatan ini menunjukkan efektivitas strategi CSR yang adaptif secara budaya dalam mempromosikan keberlanjutan lingkungan.Kata Kunci: Komunikasi CSR, Lingkungan Berkelanjutan, Pertamina